The feeling child : affect and politics in Latin American literature and film - Page, Philippa J.; Selimović, Inela; Sutherland, Camilla, 1984- (Children and youth in popular culture., 2018)
"This edited volume, working within the specific frame of the 'affective turn' in the study of contemporary sociocultural settings across Latin America, compiles a series of essays on children's presence in selected Latin American literary and cinematic expressions"--